Smart waste management for an eco environment at the housing area: article - Majidan, Muhammad Farhan (UiTM, 2020)
With the development and popularization of computer technology, digital technology, and digital equipment are the caused new system is created to eplace the previous system. In this paper, the concept of smart waste management system as a whole system is introduced. Sketchllp software is utilized to design the flow of the smart waste management system at the housing area. CX - Programmer application is used to create a program that will be transfer to the Programmable Logic Control (PLC). This system is completely program by using ladder diagram programming method. Then, the program being execute by Omron programmable controller. Then, TouchWin is interfaced with the Omron programmable controller via Universal Serial Bus (USB). TouchWin software is used to display the design flow of the system and use as Human Machine Interface (IIMI). Basically, this system will be implemented at the housing area. This system also implemented to control the smart waste management system using CX - Programmer and to reduce the carbon emission to the environment. The result from this system showed that it can help to create the better environment.